Proposed Features of a Sovereign Debt Restructuring Mechanism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper follows up on the Executive Board's December 2002 discussion of the design of the Sovereign Debt Restructuring Mechanism and seeks to make further progress on the formulation of a concrete proposal for a statutory sovereign debt restructuring mechanism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet